2018
DOI: 10.11606/issn.2238-6149.v29i2p164-169
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do desempenho de destreza manual pelo teste caixa e blocos em crianças e adolescentes brasileiros

Abstract: O teste Caixa e Blocos (TCB) tem se mostrado eficaz para avaliar a destreza manual, que se caracteriza pela capacidade das mãos e dos dedos para desempenhar uma tarefa que requer movimentos coordenados, como a manipulação de objetos sob os aspectos de velocidade, resistência e força. O objetivo desse estudo foi caracterizar o desempenho de destreza manual pelo TCB para a faixa etária de 7 a 14 anos. O estudo contou com 105 participantes, de ambos os sexos, sem apresentação de anormalidades de membro superior, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(39 reference statements)
0
1
1
Order By: Relevance
“…In addition to the correlation results, we examined prior literature for information on the expected level of manual dexterity according to age. We found that the mean values of our sample were lower than expected according to the normative data studies (Espinosa et al, 2014; Mathiowetz et al, 1985; Turco et al, 2018). Another study that evaluated fine motor skills in children also found results lower than expected for age (Gaul & Issartel, 2016).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In addition to the correlation results, we examined prior literature for information on the expected level of manual dexterity according to age. We found that the mean values of our sample were lower than expected according to the normative data studies (Espinosa et al, 2014; Mathiowetz et al, 1985; Turco et al, 2018). Another study that evaluated fine motor skills in children also found results lower than expected for age (Gaul & Issartel, 2016).…”
Section: Discussioncontrasting
confidence: 73%
“…It is not yet known, however, how the performance of movement directed at targets located in different positions in space develops over the period of middle childhood. Manual dexterity, defined as the ability to perform a coordinated task with the hands and fingers such as for object manipulation (Turco et al, 2018), is another ability that may vary with age in middle chldhood. Manual dexterity also changes with development of the neuromotor system and is typically attributed to the maturation of the corticospinal tract (Fuelscher et al, 2021).…”
Section: Introductionmentioning
confidence: 99%